1971
DOI: 10.1177/00220345710500062801
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol: Some Pharmacologic Observations

Abstract: Eugenol introduced directly into the circulatory system of the dog caused a strong but transient reduction in arterial blood pressure and myocardial contractile force, without appreciably changing heart rate or electric activity. Intra-arterial injection of the drug resulted in increased blood flow to the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…Although the action of eugenol is thought to be analgesic (Feng and Lipton, 1987;Thompson and Eling, 1989), authors reported that eugenol appears to have other actions (Sticht and Smith, 1971;Brodin and Roed, 1984). This compound reduces arterial blood pressure in dogs after intravenous injections, and increases blood flow after both intra-arterial and intravenous injections (Sticht and Smith, 1971), suggesting that the action of eugenol on the cardiovascular system might be on blood vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the action of eugenol is thought to be analgesic (Feng and Lipton, 1987;Thompson and Eling, 1989), authors reported that eugenol appears to have other actions (Sticht and Smith, 1971;Brodin and Roed, 1984). This compound reduces arterial blood pressure in dogs after intravenous injections, and increases blood flow after both intra-arterial and intravenous injections (Sticht and Smith, 1971), suggesting that the action of eugenol on the cardiovascular system might be on blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…This compound reduces arterial blood pressure in dogs after intravenous injections, and increases blood flow after both intra-arterial and intravenous injections (Sticht and Smith, 1971), suggesting that the action of eugenol on the cardiovascular system might be on blood vessels. It was also reported that methyleugenol, an analogue of the phenolic compound eugenol, relaxes the isolated ileum and inhibits contractions induced by stimulation of voltage-dependent and receptor-operated channels (Lima et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the scientific literature, too, a great variety of pharmacologi cal and toxicological data on the isolated con stituents of the volatile oil fractions are accu mulating. Eugenol is reported to show anti septic and analgesic properties {Dobbs, 1961; Kay, 1972), local anesthetic activity {Siemoneit et al" 1966), spasmolytic activity (Jurcic and Wagner, 1976), parasympathetic effects (in- O C H 3 crease in salivary gland secretion) and direct peripheral vasodilatation (Sticht and Smith, 1971). It is also shown to inhibit partially the carcinogenic effect of benzopyrene ( Van Duuren and Goldschmidt, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…This plant is known by several of its psychotropic effects in man, among them depression and states of unconsciousness (8,19,20). Animal studies also disclosed that eugenol (E) and several of its synthetic derivatives induce depression, loss of postural reflexes and potentiation of barbi turate sleeping time (10,14,15,17). Furthermore, several of these compounds revealed to be intravenous general anesthetics in humans (5,6,12).…”
mentioning
confidence: 99%